2016
DOI: 10.4236/ojog.2016.69067
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Ballooning Intracervical Catheter and Prostaglandin Pessary on Cervical Ripening

Abstract: Labor is induced to stimulate the uterine contraction in effort to have vaginal birth. Induction may be advocated to reduce fetal or neonatal morbidity and mortality. Indication of labor needs to be considered when risk and benefits analysis indicates that delivering the baby is safe option for mother or both rather than continuing the pregnancy and when there are no clear indications for caesarean section and no contraindication for vaginal delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
1
1
Order By: Relevance
“…These finding were consistent with those of Dileep P et al and Penagaluru Radha et al but contrary to the findings of Gayatri Mathuriya et al, where Dinoprostone group had significantly more minor complications [12-13-16] . Neonatal outcome did not differ significantly in our study between the two groups, similar to the studies by Anjuman et al and Krishna et al [14][15][16][17] a study by Penagaluru Radha et al showed more NICU admission in Dinoprostone group [13] .…”
Section: Discussionsupporting
confidence: 90%
“…These finding were consistent with those of Dileep P et al and Penagaluru Radha et al but contrary to the findings of Gayatri Mathuriya et al, where Dinoprostone group had significantly more minor complications [12-13-16] . Neonatal outcome did not differ significantly in our study between the two groups, similar to the studies by Anjuman et al and Krishna et al [14][15][16][17] a study by Penagaluru Radha et al showed more NICU admission in Dinoprostone group [13] .…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have reported average increase in cervical ripening in the Foleys catheter group by 5.1 scores which is lesser than our study. 11,12 The observed discrepancy may be related to the amount of water used for dilation of catheter, which was only 30 ml in contrast to 60 ml in our study. A randomized controlled trial designed to compare the rates of success with respect to volume of inflation also states that a higher volume of water used to inflate catheter increases the chances of obtaining a favourable cervix.…”
Section: Discussioncontrasting
confidence: 80%
“…Data addressing acROM rates with Foley catheter use are limited. Baloch and colleagues reported a 0% acROM rate (0/50) while Cromi experienced a 0.8% rate (2/265); neither mentioned the catheter material but probably used latex. In a large retrospective series, Maslovitz reported abandoning the procedure and removing the Foley catheter in cases of acROM — but provided no incidence data.…”
Section: Commentmentioning
confidence: 99%